NURSING CARE OF CARDIOVASCULAR SYSTEM DISORDERS UNSTABLE ANGINA PECTORIC WITH A FOCUS OF STUDY ON Mr. M at RSUD KMRT WONOSEGARA SEMARANG - Aisyah, Nurul ‘; Murdaningsih, Lia; Surnami, Surnami (Jurnal Keperawatan Respati Yogyakarta, 2022)
Unstable Angina Pectoris is chest pain or discomfort caused by coronary artery disease which describes sensations such as being pressed, squeezed, or like being pricked in the chest, caused by reversible myocardium ischemia and is caused by an imbalance between myocardial oxygen demand and myocardial oxygen supply originating from narrowing of the coronary artery astrosclerosis, signs of symptoms are: Cold sweat, nausea vomiting, difficulty breathing, anxiety and weakness, the nature of pain: pain such as pressure, burning, feeling of being crushed by heavy objects, feeling like being pierced, feeling such as squeezed and twisted, severe pain in the left chest spreads left shoulder, left neck and left upper arm, pain improves with rest or with nitrate medication. Objectives: Obtain real experience and be able to carry out comprehensive nursing care, which includes bio, psycho, social, spiritual in ustable angina pectoris clients with acute pain nursing problems in jasmine 3 RSUD KMRT Wonosegoro Semarang. The method is a case study that is to explore a problem or phenomenon with detailed limitations, has in-depth data collection and includes various sources of information. This case study was conducted on two clients, namely clients with unstable angina pectoris with acute pain nursing problems. Results: After nursing care by providing nursing intervention, nursing problems of acute pain in both clients can be overcome in part because they have not reached the desired outcome criteria. Clients with acute pain nursing problems do not always have the same response to each unstable angina pectoris client, this can be affected by the condition or health status of the previous client. So that nurses must carry out comprehensive nursing care to deal with nursing problems for each client. Keywords: Nursing Care; Acute Pain; Unstable Angina Pectoris